Repositorio Digital de la Diversidad Entomológica de la Micro Cuenca del Río Yungañan Parroquia La Esperanza periodo 2018 – 2019. - Andrade Santamaria, Jordy Patricio (2019)
The present project has the purpose of contributing to improve the visualization of the information of the digital repository between the different actors, which was developed with the PHP (Hypertext Preprocessor) methodology, ideal to make known the entomological diversity. This software allows the guest to view the information of each individual with their respective characters. It also developed three applications that contain: 1) administrator for managing the page; 2) user who can only edit and insert data to the repository and 3) guest who can consult information on entomological diversity. Concluding with the design of a database for the biodiversity of the micro-basin Yungañan River, with a collection of 640 samples, both in the forests with 11 orders grouping 89 families with an abundance of 9751 individuals and in the grasses at 10 orders grouping 80 families with an abundance of 8011 individuals. Also a digital presentation was made of the diversity of crawling insects in the sector composed of 9 levels: place (grass, forest), transect, order (characteristics), family (characteristics), photography, geographic coordinates of the sample, precipitation and harvest time.